2018
DOI: 10.1021/acs.jmedchem.7b01557
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel Small-Molecule Inhibitors of NF-κB Signaling with Antiinflammatory and Anticancer Properties

Abstract: Excessive NF-κB activation contributes to the pathogenesis of numerous diseases. Small-molecule inhibitors of NF-κB signaling have significant therapeutic potential especially in treating inflammatory diseases and cancers. In this study, we performed a cell-based high-throughput screening to discover novel agents capable of inhibiting NF-κB signaling. On the basis of two hit scaffolds from the screening, we synthesized 69 derivatives to optimize the potency for inhibition of NF-κB activation, leading to succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Investigated of chalcone, particularly that hydroxyl group in the aromatic ring did not give a significant activity (Zhang et al, 2018), but unsaturated carbonyl of chalcone predicted inhibiting the activity of transcription activity in an uncontrolled cell (Bazzaro et al, 2011) From Scheme 2, unsaturated carbonyl of chalcone attacked by Ik-kB, that it was IKK protein-mediated of the NF-kB activation pathway (Yadav et al, 2011). Based on the mechanism reaction of Scheme 2, bonding between protein Ik-kB and unsaturated carbonyl of chalcone may stop NF-kB pathway as caused proliferation of cancer cells in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Investigated of chalcone, particularly that hydroxyl group in the aromatic ring did not give a significant activity (Zhang et al, 2018), but unsaturated carbonyl of chalcone predicted inhibiting the activity of transcription activity in an uncontrolled cell (Bazzaro et al, 2011) From Scheme 2, unsaturated carbonyl of chalcone attacked by Ik-kB, that it was IKK protein-mediated of the NF-kB activation pathway (Yadav et al, 2011). Based on the mechanism reaction of Scheme 2, bonding between protein Ik-kB and unsaturated carbonyl of chalcone may stop NF-kB pathway as caused proliferation of cancer cells in humans.…”
Section: Discussionmentioning
confidence: 99%
“…For title compound, the expression rate of NO production could reach 52.19 ± 0.37%. The result showed that title compound displayed potential inhibitory effect on LPS-induced NO secretion than PDTC [8,16,17].…”
Section: Commentmentioning
confidence: 96%
“…Based on literatures, the pro-inflammatory cytokines, such as NO, TNF-α and IL-6 can trigger inflammation resulting in various diseases. If the secretion of these pro-inflammatory cytokines can be effectively suppressed, it can play a role in inhibiting inflammation [16,17]. In this study, the effect of the title compound on NO production in mouse RAW264.7 cells induced by LPS was examined by ELISA.…”
Section: Commentmentioning
confidence: 99%